Pelaksanaan Fatwa Dewan Syariah Nasional tentang Layanan Pembiayaan Berbasis Teknologi Informasi Berdasarkan Prinsip Syariah Pada Perusahaan Fintech Syariah - Hadrianto, Muhammad Septian; Angga, La Ode; Fataruba, Sabri (Faculty of Law, Universitas Pattimura, 2022)
Introduction: In the decision of the DSN Fatwa Number 117/DSN-MUI/II/2018 part two point 2 of the fatwa it is also stated that the implementation of information technology-based financing services based on sharia principles must follow the provisions contained in this fatwa. but in fact there are still Sharia Fintech Companies that have not fully implemented the DSN-MUI fatwa as was done by PT. Indonesian Sharia Funds that still provide interest to the recipient of financing for the sharia products they offer.Purposes of the Research: The purpose of this study is 2 (two), namely to analyze and review the implementation of the DSN-MUI Fatwa Number 117/DSN-MUI/II/2018 on Sharia Fintech companies and to analyze and examine the legal strength of the DSN MUI Fatwa Number 117/DSN-MUI /II/2018 in binding Sharia Fintech Companies. Methods of the Research: The type of research is normative juridical, with two approaches, namely the conceptual approach and the statutory approach.Results of the Research: The results of this study indicate that in previous research conducted by Ferdian Mahmuda, sharia fintech companies were found which in implementing the Fatwa DSN MUI Number 117/DSN-MUI/II/2018 did not apply it thoroughly and classified as violating the provisions set by the MUI. The National Sharia Council, therefore the MUI Fatwa still has legal force as long as a financial institution in its financial activities implements sharia principles, including in this case a Sharia Fintech company, so that if its financial operational activities conflict with sharia principles, the DPS will report to DSN, then DSN recommends the violation to OJK to take action as regulated in Financial Services Authority Regulation (POJK) Number 77 of 2016 concerning Information Technology-Based Lending and Borrowing Services CHAPTER XII Article 47, which contains administrative sanctions tration to be provided to the financial institution referred to by OJK.